Case report: VEXAS as an example of autoinflammatory syndrome in pulmonology clinical practice - Więsik-Szewczyk, Ewa; Zegadło, Arkadiusz; Sobczyńska-Tomaszewska, Agnieszka; Korzeniowska, Marcelina; Jahnz-Rózyk, Karina (Frontiers in Medicine, 2024)
Lung involvement is not widely recognized as a complication of auto-inflammatory diseases. We present a broad approach to diagnose a severe form of autoinflammatory syndrome in an adult male patient. A 63-year-old Caucasian male presented with recurrent episodes of high fever, interstitial lung infiltration, and pleural effusion. Laboratory tests performed during the flares revealed lymphopenia and increased levels of C-reactive protein and ferritin. Broad diagnostic research on infections, connective tissue diseases, and malignancies yielded negative results. The patient’s symptoms promptly resolved upon the administration of glucocorticoids; however, they reappeared when the prednisone dose was reduced. All attempts to administer immunomodulatory and immunosuppressive medications were ineffective. During follow-up, autoinflammatory syndrome was suspected; however, no pathological variants of monogenic autoinflammatory diseases were identified by genome-exome sequencing. The patient did not respond to interleukin 1 blockade with anakinra. He died due to multi-organ failure, and his condition remained unresolved until the first reported description of vacuole, E1 enzyme, X-linked, autoinflammatory, and somatic syndrome (VEXAS). We describe the diagnostic traps and reasoning process involved in establishing that the patient’s symptoms were autoinflammatory in nature based on clinical symptoms, in addition to the proof of concept gained from genetic reevaluation and identification of pathogenic variants in the UBA1 gene. The aim of this review is to increase the awareness of VEXAS among pulmonologists. Genetic screening for UBA1 should be considered in patients with recurrent pneumonitis of unknown origin with elevated inflammatory markers and signs of cytopenia, especially if they require chronic steroids to control the disease. Respiratory manifestations are part of VEXAS; these may be dominant in the course of the disease and severe at presentation.